2013
DOI: 10.1155/2013/519619
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Cellular Biomarkers in the Diagnosis of Cervical Intraepithelial Neoplasia and Cancer

Abstract: Cervical cancer arises from cells localized in the ectoendocervical squamocolumnar junction of the cervix persistently infected with one of about 13 human papillomavirus (HPV) genotypes. The majority of HPV infections induces low grade squamous epithelial lesions that in more than 90% of cases spontaneously regress and in about 10% eventually progress to high grade lesions and even less frequently evolve to invasive cancer. Tumor progression is characterized by (1) increased expression of E6 and E7 genes of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 72 publications
1
89
0
7
Order By: Relevance
“…That marker might be used to reduce the number of women referred to a more careful monitoring and follow-up regime, raising the specificity of assessment in women with atypical squamous cells of undetermined significance (ASC-US) and low-grade squamous intraepithelial lesions (LSILs) (Varnai et al, 2008;Keegan et al, 2009;Brown and Trimble, 2012;Tornesello et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…That marker might be used to reduce the number of women referred to a more careful monitoring and follow-up regime, raising the specificity of assessment in women with atypical squamous cells of undetermined significance (ASC-US) and low-grade squamous intraepithelial lesions (LSILs) (Varnai et al, 2008;Keegan et al, 2009;Brown and Trimble, 2012;Tornesello et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of TOP2A was identified in cervical cancer using different high-throughput expression profiling technologies (22). The TOP2A and MCM2 genes have been identified as molecular markers for the diagnosis of cervical cancer (23,24). Similar studies have also demonstrated that TOP2A was upregulated in cervical cells and tissues with elevated expression of the HPV E6/E7 proteins (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of p16 and Ki-67 have proven to be useful indicators of clinically significant infections and lesion severity in numerous studies (11,18,19); several properties of p16 and Ki-67 enable them to be promising biomarkers for HPV-associated cancer, since they are associated with histological grade and infection for HR-HPV (17). In addition, p16 immunostaining appears to be a useful adjunctive test in the examination of colposcopically-directed cervical biopsies and in the diagnostic cascade of women investigated for abnormal Papanicolaou smears, due to its capacity to reveal the integration of high-risk HPV DNA into the host cell genome (20).…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is a non-histone protein that exists as two isoforms encoded by cDNA sequences of 11.5 and 12.5 kb organized over 15 exons and localized on chromosome 10 (9). Its expression is applied to assess the growth fraction of a cell population (10 (11,12). Based on the aforementioned data, the present study evaluated Ki-67 and p16 immunostaining in CIN lesions diagnosed in pregnancy compared with those diagnosed in non-pregnant women.…”
Section: Introductionmentioning
confidence: 99%